Environmental context-dependent activation of dopamine neurons via putative amygdala-nigra pathway in macaques - Kazutaka Maeda; Ken-ichi Inoue; Masahiko Takada; Okihide Hikosaka (Nature Communications, 2023)
Abstract Seeking out good and avoiding bad objects is critical for survival. In practice, objects are rarely good every time or everywhere, but only at the right time or place. Whereas the basal ganglia (BG) are known to mediate goal-directed behavior, for example, saccades to rewarding objects, it remains unclear how such simple behaviors are rendered contingent on higher-order factors, including environmental context. Here we show that amygdala neurons are sensitive to environments and may regulate putative dopamine (DA) neurons via an inhibitory projection to the substantia nigra (SN). In male macaques, we combined optogenetics with multi-channel recording to demonstrate that rewarding environments induce tonic firing changes in DA neurons as well as phasic responses to rewarding events. These responses may be mediated by disinhibition via a GABAergic projection onto DA neurons, which in turn is suppressed by an inhibitory projection from the amygdala. Thus, the amygdala may provide an additional source of learning to BG circuits, namely contingencies imposed by the environment.